Yield and income security through improved millet and allied farming in dryland area of Telangana - Chapke, Rajendra R.; Srinivas, A.; Anuradha, N.; Swarna, R.; Priyanka, V. (Indian Farming, 2025)
Farmer FIRST Programme has been providing a platform to bring scientists and farmers together where farmers’ problems are identified, and development of location specific, farmer friendly and need-based technological options for enhancing famers’ income as well as livelihood security through participatory approach are prioritized. This article describes the performance of various interventions under five modules of the project. There was an increase in yields ranging 16-40% and net returns 27-57% compared to farmers’ practice from the crop module interventions. From livestock and horticulture modules, nutritional and income security was achieved with net returns ranging between ` 10,000 to 36,900 and ` 1,100 to 1,500, respectively. The enterprise module also helped the farmers in employment generation through processing and value-addition.